Assessment of the overall energy performance of an SPD smart window in a hot desert climate. (1st August 2022) - Mesloub, Abdelhakim; Ghosh, Aritra; Touahmia, Mabrouk; Albaqawy, Ghazy Abdullah; Alsolami, Badr M.; Ahriz, Atef
Abstract: In this study, the overall energy consumption and visual comfort of a switchable suspended particle device (SPD) smart window were investigated as part of the glazing integration of an adaptive building designed to consume less energy in a hot desert climate. A typical floor of a commercial office building in Riyadh was chosen for the energy and visual comfort simulation, which was based on Energy-Plus and Diva-for-Rhino software for cardinal orientation. A comprehensive simulation analysis of various state of SPD glazing, namely opaque (OFF), transparent (ON) and automated controlled (based on solar radiance: from 100w/m 2 – 900w/m 2 ), was conducted and the results were compared against traditional single glazing and double-glazing low emissivity (DG low-e) coated windows for reference. The simulation results indicated that switchable SPD smart windows (in the OFF and automated states) achieved a promising reduction of net energy by up to 58% against DG low-e, apart from at the northern orientation. Conversely, the opaque (OFF state) had a counterproductive impact on lighting energy consumption and visual comfort. Acceptable daylight autonomy (DA300lux ) and Useful daylight illuminance (UDI100lux–2000lux ) was observed for the SPD smart window in the ON and automated controlled states; moreover, it offered a significant reduction in daylight glare probability (DGP). Thus, controlled switchable SPD glazing can be a good alternative to standard glazing in a hot desert climate in terms of reducing energy use and providing visual comfort. Highlights: Visual comfort of SPD with different states was evaluated for an office building. The energy performance of SPD was performed comparing DG low-E under hot climate. Raytracing simulations of automated SPD enhance indoor illuminance and reduce glare. SPD Controlled state with <100 W/m2 attained the highest annual energy reduction.